Towards More Effective Global Drug Policies - Chatwin, Caroline (Springer International Publishing, 2018)
This book examines the topical issue of global drug policy and outlines five steps that could be taken to improve its effectiveness. A public criminology approach is applied to explore not only what could be done, but also why it matters and how it could be achieved. It argues that more effective global drug policies require an acknowledgement of the failure of a war on drugs approach and the harms it has caused. Instead, strategies that reduce drug related harm should be prioritised. An innovative and diverse range of approaches should be developed that are underpinned by evaluation and dissemination of results. Finally, the horizons of the drug policy debate should be broadened. In line with the central aims of public criminology, this book provides an accessible contribution to global drug policy debates that links theory and practice and which will have appeal to a wide range of audiences.